Evaluating habitat suitability and connectivity for a recolonizing large carnivore. (February 2020) - Hemmingmoore, Heather; Aronsson, Malin; Åkesson, Mikael; Persson, Jens; Andrén, Henrik
Abstract: The conservation of wide-ranging species presents challenges in a world of intensified human land use, forcing animals to occupy and recolonize human-modified landscapes. Although identifying suitable habitat and ensuring connectivity are important in supporting natural recolonization, these actions are rarely validated due to difficulties in monitoring such events. In Sweden, the Eurasian lynx (Lynx lynx) is now recolonizing its former range, after centuries of persecution. We investigated resource selection based on telemetry data from 108 lynx monitored over 20 years. We assessed the differences between the established population in central Sweden and the recolonizing population in southern Sweden, and between established and dispersing individuals. We found that models based on central Sweden successfully identified core habitat patches for establishment in southern Sweden, validated after recolonization. We also found that lynx selected for higher habitat suitability during the recolonization phase, and that dispersing individuals were less selective than established lynx. Using cost-distance analysis, we assessed connectivity between central and southern Sweden, and found that landscape permeability was higher when based on dispersing lynx compared to established lynx. Altogether, our findings suggest that when landscapes are sufficiently similar between source and recolonization areas, resource selection information from an established population can be useful for managers seeking to facilitate recolonization of wide-ranging species. We recommend more frequent use of validation during and after recolonization events, to improve our common understanding of habitat suitability and connectivity modeling, and therefore to enable more active management of recolonization events.